Penerapan Psikoedukasi untuk Meningkatkan Motivasi Belajar Siswa di SDN 10 Suka Tani - Siti Nurhalizah; Desy Arisandy (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
The main problem faced at SDN 10 Suka Tani Village is the low learning motivation of elementary school students, which is indicated by a lack of enthusiasm for learning, low class participation, and a tendency to get bored easily and be passive in completing assignments. This condition is influenced by the lack of special programs that focus on strengthening learning motivation and limited support for the learning environment. This community service activity aims to increase student learning motivation through the implementation of psychoeducation that is educational, interactive, and in accordance with the developmental characteristics of elementary school students. The methods used include observation, interviews with teachers and students, and the implementation of psychoeducation through motivational lectures, group learning activities, and the use of educational posters. The activity was carried out in five meetings targeting fourth-grade students at SDN 10 Tanjung Lago. The results of the activity showed an increase in students' understanding of the importance of learning, increased courage to ask questions, active participation in learning activities, and the emergence of positive attitudes such as greater focus, discipline, and self-confidence. In conclusion, the implementation of psychoeducation has proven effective as a promotive and preventive effort in increasing learning motivation of elementary school students and can be used as an alternative learning support program in elementary schools.